Residual nitrite and nitrate in processed meats and meat analogues in the United States - Siyuan Sheng; Erin M. Silva; Rodrigo Tarté; James R. Claus (Scientific Reports)
Abstract Residual nitrite (NO2 −) and nitrate (NO3 −) have been widely studied in the past few decades for their function to improve processed meat quality and their impact on human health1–4. In this study we examined how the residual nitrite and nitrate (NOx −) content of major classes of processed meats products (n = 1132) produced locally from three regions (East Coast, Midwest and West Coast) and plant protein-based meat analogues (n = 53) available at retail in the United States was influenced by their composition, processing, and geographical attributes. We also conducted time-dependent depletion studies and observed different patterns of NOx − depletion and conversion during processing and storage and correlated them with product quality. Together, our results reveal a comprehensive prospective of NOx − content in processed meats and meat analogues. The NO2 − in processed meats and meat analogues averaged (± standard error; minimum and maximum value in parentheses) 13.7 ± 0.62 (0.0-214.5) and 1.7 ± 0.34 (0.0–11.0), respectively, and the NO3 − in processed meats and meat analogues averaged 32.6 ± 0.90 (2.0–205.9) and 7.2 ± 0.56 (4.0-25.3) ppm, respectively.